The effect of employee share ownership on company performance in South African mining - Khan, Shameegh (University of the Witwatersrand, Johannesburg, 2014)
This study investigates the effects of Employee Share Ownership Plans (ESOP’s) on company profitability in the South African mining industry for companies listed on the Johannesburg Stock Exchange (JSE). The South African mining industry has been in the global spotlight since the Marikana miners’ strike of 2012 and the subsequent killing of 34 people on 16 August 2012. ESOP’s can be used to stabilize the sector by alleviating some of the tension that is present between workers, shareholders, management and government. This research uses the same measurement as Spiess and Affleck-Graves (1995), who measure share price performance as a cumulative average of returns (CAAR) over a five year period. Regression analysis is used to test for correlations and descriptive statistics is used to explain findings (Spiess & Affleck-Graves, 1995). The difference between companies that do not have ESOP’s in place is negative for (CAAR) compared to those who have an ESOP in place. This is consistent with the theory and findings of studies such as Robinson and Zhang (2005). It has been applied to the South African context within the JSE listed mining sector. The theory that ESOP’s will improve profitability of a company listed on the JSE within South African mining has been found to be statistically significant. ESOP’s can help improve cumulative profits and help transform the industry through share ownership of workers which will help decrease the gap between CEO’s remunerations and the lowest paid workers.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Business Administration, in the Wits Business School, in 2014.
Keywords: Employee Share Ownership Plans (ESOP’s); South African mining industry; Johannesburg Stock Exchange (JSE); Marikana miners’ strike of 2012; Share ownership of workers; Lowest paid workers; CEO’s remunerations; UCTD